Synthesis of industrially relevant carbamates towards isocyanates using carbon dioxide and organotin(IV) alkoxides - Germain, Nicolas; Müller, Imke Britta; Hanauer, Matthias; Paciello, Rocco; Baumann, Robert; Trapp, Oliver; Schaub, Thomas (ChemSusChem, 2016)
Abstract A straightforward phosgene-free synthesis of aromatic isocyanates and diisocyanates is disclosed. Theoretical investigations suggested that the insertion of carbon dioxide (CO2) by dialkyltin(IV) dialkoxides could be used to convert aromatic amines into aromatic mono- and dicarbamates. Here we show, that methyl phenylcarbamate (MPC) from aniline using organotin(IV) dimethoxide and CO2 can be formed in high yield of up to 92?%, experimentally corroborating the predictions of density functional theory (DFT) calculations. MPC was then separated from the tin oxide residues and converted into phenyl isocyanate. Furthermore, organotin(IV) alkoxides could be regenerated from the tin oxide residues and reused, paving the way for a continuous industrial process. Extension of the scope to the synthesis of diurethanes from toluene 2,4-diamine and 4,4?-methylenedianiline could potentially allow the efficient production of industrially relevant diisocyanates.
Gesehen am 03.06.2020